Ba2InTaO6 – A Partially B‐Site‐Ordered Double Perovskite for Overall Water Splitting. Issue 35 (13th November 2015) - Song, Kai; Yang, Jia; Jiang, Pengfei; Gao, Wenliang; Cong, Rihong; Yang, Tao
Abstract: Completely B‐site‐ordered Ba2 InTaO6 has been prepared previously by prolonged heating at 1500 °C; here, we significantly lowered the annealing temperature to 1130 °C under H2 /Ar dynamic flow and obtained a partially ordered (ca. 74 %) double perovskite, as determined by Rietveld refinement of the powder X‐ray diffraction data. As a wide‐band‐gap semiconductor, Ba2 InTaO6 possesses photocatalytic activity for overall water splitting under UV irradiation, though the gas evolution rates of 12.9 and 6.6 μmol/h/g for H2 and O2 generation, respectively, are low. With the assistance of methanol as a sacrificial reagent, the H2 evolution rate increases to 50.5 μmol/h/g, which indicates that the surficial charge recombination rate is really high. We applied the typical cocatalyst‐loading method to this material, and with 1 wt.‐% PtO x and NiO x, the H2 production rates in pure water were further improved to 16.0 and 18.4 μmol/h/g, respectively. Attempts to dope Ba2 InTaO6 with first‐row transition metals (Ti, V, Cr, Mn, Fe, Co, and Ni) led to a general enhancement of the light‐harvesting ability; however, the experimental water‐splitting activity did not improve. We believe that the doped cations most likely behaved as recombination centers for photogenerated charges. Considering its structural similarity to the well‐known catalyst InTaO4 :Ni, Ba2 InTaO6 possesses the potential to extend its photocatalytic activity to the visible‐light region but needs further enhancement. Abstract : The partially B‐site‐ordered double perovskite Ba2 InTaO6 is prepared by annealing the raw materials at 1130 °C under H2 /Ar flow. It possesses an InO6 –TaO6 framework and, therefore, exhibits substantial photocatalytic activity for overall water splitting into stoichiometric H2 and O2 under UV light.